2011
DOI: 10.1111/j.1464-0597.2011.00453.x
|View full text |Cite|
|
Sign up to set email alerts
|

Flexible Work Arrangements Availability and their Relationship with Work‐to‐Family Conflict, Job Satisfaction, and Turnover Intentions: A Comparison of Three Country Clusters

Abstract: The present study explored the availability of flexible work arrangements (FWA) and their relationship with manager outcomes of job satisfaction, turnover intentions, and work-to-family conflict (WFC) across country clusters. We used individualism and collectivism to explain differences in FWA availability across Latin American, Anglo, and Asian clusters. Managers from the Anglo cluster were more likely to report working in organisations that offer FWA compared to managers from other clusters. For Anglo manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
170
1
25

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(200 citation statements)
references
References 52 publications
4
170
1
25
Order By: Relevance
“…Haar 2008;Behson 2005), or have even found that FWPs decrease organizational attachment (e.g. Masuda et al 2012). Hence, a meta-analytic summary is important to provide clear insights on the links between FWPs and organizational attractiveness and organizational attachment, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Haar 2008;Behson 2005), or have even found that FWPs decrease organizational attachment (e.g. Masuda et al 2012). Hence, a meta-analytic summary is important to provide clear insights on the links between FWPs and organizational attractiveness and organizational attachment, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in psychological well-being have often been linked to different occupational groups (Batinic, Selenko, Stiglbauer, & Paul, 2010;Masuda et al, 2012). If some organizational and task related characteristics (e.g.…”
Section: Work Alienation and Occupational Statusmentioning
confidence: 99%
“…A theoretical perspective that explains the employer's perceptions on workplace flexibility for workers has been presented by institutional theory (Masuda et al, 2012), which postulates that organizations must adapt to pressures from the environment, such as cultural expectations.…”
Section: Theories and Models Of Workplace Flexibilitymentioning
confidence: 99%